Desarrollo e implementación del portal web unidad educativa “la asuncion” - Guerrero Zambrano, Erick (2010)
The Special Education Unit "Assumption", consists of: the school and the Experimental College "Assumption." Private School and the Experimental College "The Assumption" are morning and mixed schools, with the following work schedules: School: 07h30 to 12h40. College: 07h00 to 13h30. Many formative years of comprehensive training of children and adolescents have made the unit, a prestigious institution and preferred by parents for the education of their children. Considering the technological advances in the educational in regard to the Internet, the directors decided that the institution has an internet presence through the development and implementation of a web portal www.laasuncion.edu.ec, showing the world the services school and college education for children and youth and thus compete strongly with other agencies providing similar services. The Internet as a complementary channel in the educational process, immerse the students in the use of this technology, making an early age can use the computer or a cellular device and the tasks or download content, send communications to managers, teachers or leaders of course, learn about activities that the institution performs as part of the planning of the school year, both academic, sporting or integration. This will achieve better interaction between parents, teachers and students, in a more dynamic and secure using technological means and thus better training of its students.